Perancangan Sistem Pakan Ikan Pada Akuarium Berbasis Internet Of Things - Hidayat, Muhammad Taufiq (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The development of IoT technology has brought innovation in automatic fish feeding systems. This research was conducted at the Zahra Aquarium Ornamental Fish Store, which experienced obstacles in feeding due to limited staff and inconsistent schedules. To overcome this problem, an IoT-based automatic system was designed using NodeMCU ESP8266, infrared sensors, and Telegram notifications. This system allows scheduled feeding and automatic stock monitoring, so that fish maintenance becomes more efficient and scheduled. The prototype method was used in its development, and the test results showed that this system can increase the effectiveness of feeding and stock monitoring.